Extraction of mangiferin from Mahkota Dewa (Phaleria macrocarpa) using subcritical water - Kim, Wan-Joo; Veriansyah, Bambang; Lee, Youn-Woo; Kim, Jaehoon; Kim, Jae-Duck (ELSEVIER SCIENCE INC, 2010)
A pharmacological active component, mangiferin, was extracted from Mahkota Dewa using subcritical water extraction. The subcritical water extractions were carried out at temperatures ranging 323-423 K, pressures ranging 0.7-4.0 MPa, and extraction times ranging 1-7 h. Extraction yield of mangiferin was measured using high-performance liquid chromatography (HPLC). The extraction yield was strongly dependent on the temperature while weakly dependent on the extraction pressure. As the extraction temperature increased, the extraction mangiferin yield increased, possibly resulting from the decrease in polarity of subcritical water at higher temperature. At an optimal extraction condition of 373 K, 4.0 MPa and extraction time of 5 h, the extraction yield of mangiferin was 21.7 mg/g. This value was close to the extraction yield with methanol (25.0 mg/g) and higher than those with water (18.6 mg/g) or ethanol (13.2 mg/g) at their boiling points. (C) 2010 Published by Elsevier B.V. on behalf of The Korean Society of Industrial and Engineering Chemistry.
Keywords: SUPERCRITICAL-FLUID EXTRACTION; CARBON-DIOXIDE; TEMPERATURES; SOLUBILITY